Propolis to Curb Lifestyle Related Disorders: An Overview. Issue 2 (1st February 2016) - Saeed, Farhan; Ahmad, Rabia Shabir; Arshad, Muhamad Umair; Niaz, Bushra; Batool, Rizwana; Naz, Rabia; Ansar Rasul Suleria, Hafiz
Abstract : The natural products are gaining immense importance in the domain of nutrition to prevent various maladies and improve the quality of life. Among these, natural exudates are of significant worth as these biochemical compounds are released by various living entities having pharmacological properties for utilization in various drug developments. These natural exudates are the promising source for the discovery of new medications. Numerous bioactive moieties collected by honeybees from exudates and buds of particular trees and plants, considered to be utilized as defensive barrier with special reference to propolis. It generally contains numerous biochemical components, i.e., polyphenols, steroids, terpenoids, and amino acids. They also contain isoferulic acid, sinapinic acid, caffeic acid, and chrysin responsible for antibacterial perspectives. With special attention to propolis, it has been utilized in folk medicines due to several of its therapeutic activities, i.e., antioxidant, antidiabetic, anti-inflammatory, antiviral, and anticancer properties. In this context, it is extensively used in foodstuffs and beverages to improve health related disorders like inflammation, diabetes, heart disease, protects injured gums, and cancer insurgence. Moreover, it has been used to curtail stomatology, gastroenterology, skin lesions, and otorhinolaryngologic and respiration diseases.